Facile synthesis, crystal structure, biological evaluation, and molecular modeling studies of N-((4-acetyl phenyl) carbamothioyl) pivalamide as the multitarget-directed ligand - Saeed, Aamer; Ejaz, Syeda Abida; Khalid, Aqsa; Channar, Pervaiz Ali; Aziz, Mubashir; Wani, Tanveer A.; Zargar, Seema; Hassan, Sidra; Ismail, Hammad; Khalid, Dania; Hashmi, Muhammad Zaffar; Hökelek, Tuncer; et al. (Frontiers in Chemistry, 2022)
The crystal structure of N-((4-acetylphenyl)carbamothioyl)plvalamide (3) was synthesized by inert refluxing pivaloyl isothiocyanate (2) and 4-aminoacetophenone in dry acetone. The spectroscopic characterization (1H-NMR, 13CNMR, FT-IR) and single crystal assays determined the structure of synthesized compound (3). Systematic experimental and theoretical studies were conducted to determine the molecular characteristics of the synthesized crystal. The biological examination of (3) was conducted against a variety of enzymes i.e., acetyl cholinesterase (AChE), butyl cholinesterase (BChE), alpha amylase, and urease enzyme were evaluated. The crystal exhibited approximately 85 % enzyme inhibition activity against BChE and AChE, but only 73.8 % and 57.9 % inhibition activity against urease and alpha amylase was observed respectively. The theoretical calculations were conducted using density functional theory studies (DFTs) with the 6-31G (d, p) basis set and B3LYP functional correlation. The Frontier molecular orbital analysis revealed that the HOMO/LUMO energy gap was smaller, which corresponds to the molecule's reactivity. In terms of reactivity, the chemical softness value was found to be in good agreement with experimental values. In Crystal structure analysis, the intramolecular N—H•••O hydrogen bond generates a S (6) ring motif and N—H•••O interactions exist in crystal structure between the centroids of neighboring parallel aromatic (C4-C9) rings with a centroid to centroid distance of 3.9766(7)Å. These intermolecular interactions were useful in structural stabilization. The Hirshfeld surfaces and their related two-dimensional fingerprint plots were used for thorough investigation of intermolecular interactions. According to Hirshfeld surface analysis of the crystal structure the most substantial contributions to the crystal packing are from H ••• O and H ••• N/N ••• H interactions. Molecular docking studies were conducted to evaluate the binding orientation of synthesized crystal with multiple targets. The compound exhibited stronger interactions with AChE and BChE with binding energies of -7.5 and -7.6 kcal/mol, respectively. On the basis of in-vitro and in-silico findings, it is deduced that N-((4-acetylphenyl)carbamothioyl)pivalamide (3) possesses reactive and potent multiple target inhibitory properties.